2020
DOI: 10.1038/s41467-020-16744-1
|View full text |Cite
|
Sign up to set email alerts
|

Proximity labeling proteomics reveals critical regulators for inner nuclear membrane protein degradation in plants

Abstract: The inner nuclear membrane (INM) selectively accumulates proteins that are essential for nuclear functions; however, overaccumulation of INM proteins results in a range of rare genetic disorders. So far, little is known about how defective, mislocalized, or abnormally accumulated membrane proteins are actively removed from the INM, especially in plants and animals. Here, via analysis of a proximity-labeling proteomic profile of INM-associated proteins in Arabidopsis, we identify critical components for an INM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…PUX3-5 were additionally shown to interact with CRWN4 and KAKU4. Treatment with a proteasome inhibitor, MG132, resulted in an increase in SUN1 accumulation, confirming SUN1 is a target of proteasome degradation98 . Loss-of-function mutants for PUX3-5 resulted in an increase in SUN1protein, suggesting PUX3-5 negatively regulate SUN1 degradation98 .…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…PUX3-5 were additionally shown to interact with CRWN4 and KAKU4. Treatment with a proteasome inhibitor, MG132, resulted in an increase in SUN1 accumulation, confirming SUN1 is a target of proteasome degradation98 . Loss-of-function mutants for PUX3-5 resulted in an increase in SUN1protein, suggesting PUX3-5 negatively regulate SUN1 degradation98 .…”
mentioning
confidence: 78%
“…Treatment with a proteasome inhibitor, MG132, resulted in an increase in SUN1 accumulation, confirming SUN1 is a target of proteasome degradation98 . Loss-of-function mutants for PUX3-5 resulted in an increase in SUN1protein, suggesting PUX3-5 negatively regulate SUN1 degradation98 . It remains to be determined if PUX3-5 interface with and regulate INM proteins generally, or SUN proteins specifically and what role the interaction with CRWN4 and KAKU4 plays in this process.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In 2019, Wong's group used BioID-based PL to identify the interaction partners of autophagy-related protein 8 (ATG8) and the 126 kDa replicase of tobacco mosaic virus (TMV) ( Das et al., 2019 ; Macharia et al., 2019 ). Very recently, Yangnan Gu's group used BioID2-based PL to profile the plant nuclear envelope and inner nuclear membrane proteomes in Arabidopsis ( Huang et al., 2020 ). They identified a novel component of the nuclear pore complex and unraveled critical regulators of inner nuclear membrane protein degradation, all of which enhance our understanding of the composition of subnuclear structures and the underlying functions of nuclear membrane-associated proteins ( Huang et al., 2020 ; Tang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Yangnan Gu's group used BioID2-based PL to profile the plant nuclear envelope and inner nuclear membrane proteomes in Arabidopsis ( Huang et al., 2020 ). They identified a novel component of the nuclear pore complex and unraveled critical regulators of inner nuclear membrane protein degradation, all of which enhance our understanding of the composition of subnuclear structures and the underlying functions of nuclear membrane-associated proteins ( Huang et al., 2020 ; Tang et al., 2020 ). These studies reinforced the robustness of PL methods for identifying membrane-associated interaction partners, which are inaccessible by traditional approaches, and indicated that PL methods could also be used to investigate global sub-organelle proteomes in plant systems as in mammalian cells ( Kim et al., 2016 ; Cho et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%